"From the Australian Bush to the International Jungle" Internationale Karrieren und der Völkerbund - Auberer, Benjamin (Heidelberg University Publishing (heiUP), 2023)
After World War I, membership in the League of Nations represented an important step for the British Dominions on the road to foreign policy independence. The internationalism of the League of Nations was not a purely political phenomenon, but also had a social dimension. In particular, the Geneva based Secretariat of the League of Nations evolved into a hub of liberal internationalism. Benjamin Auberer examines these networks by investigating the careers of five employees of the League of Nations from Australia and New Zealand and thus contributes to a global history of the League of Nations and its bureaucracy.